Anti-restriction functions of injected phage proteins revealed by peeling back layers of bacterial immunity - Sukrit Silas; Héloïse Carion; Kira S. Makarova; David Sanchez Godinez; Surabhi Haniyur; Lucy Volino; Wearn-Xin Yee; Andrea Fossati; Danielle Swaney; Michael Bocek; Eugene V. Koonin; Joseph Bondy-Denomy (Nature Communications)
Abstract Virus-host competition drives evolution of diverse antivirus defenses, but how they co-operate in wild bacteria and how bacteriophages circumvent host immunity remains poorly understood. Here, using a functional screening platform to systematically explore the functions of phage accessory genes, we describe how cell-surface barriers can obscure the phenotypes of intracellular defenses in E. coli isolates. LPS modification emerged as a major theme, with the discovery of several small phage proteins that modify specific O-antigen structures, removing barriers to phage adsorption. Bypassing O-antigen in wild E. coli strains revealed another layer of defense: Type IV restriction endonucleases (RE) that target modified DNA of T-even phages (T2, T4, T6). We further show how injected proteins Ip2 and Ip3 of T4 inhibit distinct subtypes of these Type IV REs. Extensive variability in Type IV REs likely drives the emergence of subtype-specific inhibitors through multiple rounds of adaptation and counter-adaptation.